The Correlation between Language Acquisition and Language Planning - Ramlan Ramlan (Budapest International Research and Critics University, 2018)
Language acquisition is a process which can take place at any period of one's life. In the sense of first language acquisition, however, it refers to the acquisition (unconscious learning) of one's native language (or languages in the case of bilinguals) during the first 6 or 7 years of one's life (roughly from birth to the time one starts school).Language acquisition planning has a significant correlation to the language acquisition by the students. Because the students’ age in between zero up to five years is the appropriate moment to acquire a certain language.